Simulation of Heat Transfer in Cylinder Husks Furnace with Finite Difference Method. Issue 1 (January 2016) - Noor, I; Irzaman,; Syafutra, H; Ahmad, F
Abstract: Simulation of heat transfer on cylinder husk furnace with FDM (Finite Difference Method) has been performed. This simulation aimed to study the heat transfer based on conduction and convection mechanism on the cylinder husk furnace. Fluid dynamics inside the cylinder of husk furnace was obtained by solving the Navier-Stokes equations with laminar flow approach. The initial temperature in all parts of the cylinder is room temperature, except at the bottom of the cylinder is 491 o C. Through numerical calculation of heat conduction and convection equation by FDM method, we got that the velocity of fluid flow is ranged between 3:32 - 13.75 m/s and 2:00 - 13.75 m/s for fixed and unfixed temperature of the cylinder blanket, respectively.